PROFIL KONDISI FISIK ATLET PORPROV CABANG OLAHRAGA BOLA VOLI PUTRA KOTA PANGKALPINANG TAHUN 2023 - Sigit Pra Yoga; Andriadi Andriadi; Muhammad Eka Mardyansyah Simbolon (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The reason for this study was to decide the actual wellness of male Porprov volleyball competitors contending in Pangkalpinang City in 2023. Arm muscle strength, leg muscle strength, arm muscle endurance, lung and heart muscle endurance, endurance abdominal muscle strength, arm muscle power, leg muscle power, speed, and flexibility were the limited physical conditions in this study. This quantitative descriptive study The number of inhabitants in this study were all Pangkalpinang Porprov volleyball competitors in 2023, adding up to 12 competitors. This study employs a saturated sampling strategy and uses the entire population as the sample. Measurements and tests are used in data collection techniques. According to the findings of the data analysis on the physical condition of Porprov athletes participating in the men's volleyball sport in Pangkalpinang City in 2023, there are zero athletes who are in poor physical condition (zero percent), zero athletes who are in adequate physical condition (zero percent), and 12 athletes who are in good physical condition (100 percent). There are no athletes in the very good category (0 percent) or in perfect physical condition (0 percent). According to the data, the average score of 24.58 falls into the good category, with the lowest score being 22 (minimum) and the highest being 28 (maximum).